2005
DOI: 10.1002/cncr.20809
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the status of axillary sentinel lymph nodes in 4351 patients with invasive breast carcinoma treated in a single institution

Abstract: BACKGROUND. Reliable predictors of metastatic involvement would enable a better selection of candidate patients for sentinel lymph node biopsy (SLNB) and possibly allow identification of patients with such a low risk of axillary sentinel lymph node (SLN) involvement to be even spared SLNB. METHODS. The authors evaluated 4351 consecutive patients surgically treated for breast carcinoma who also underwent SLNB. Clinicopathologic features significantly associated with SLN metastases by univariate analysis were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
139
6
15

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(195 citation statements)
references
References 28 publications
29
139
6
15
Order By: Relevance
“…Ductal carcinomas carried a higher risk. On the other hand, lobular carcinomas and better prognosis tumor types (cribriform, medullary, mucinous, and tubular) showed a lower incidence of metastatic lymph nodes (28). Small occult metastases were detected in 13% of the cases, consistently with earlier reports (5, 6, 8 -11, 24), and were more frequent in lobular than in ductal carcinomas (Table 1), consistent with previous reports (10,13).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Ductal carcinomas carried a higher risk. On the other hand, lobular carcinomas and better prognosis tumor types (cribriform, medullary, mucinous, and tubular) showed a lower incidence of metastatic lymph nodes (28). Small occult metastases were detected in 13% of the cases, consistently with earlier reports (5, 6, 8 -11, 24), and were more frequent in lobular than in ductal carcinomas (Table 1), consistent with previous reports (10,13).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies (28), histologic tumor types were found to correlate with the likelihood of macroscopic lymph node metastases. Ductal carcinomas carried a higher risk.…”
Section: Discussionsupporting
confidence: 89%
“…Positive expression for ER and PR was significantly correlated with histological grade, mitotic score and nuclear pleomorphism [16]. In one of the series it has been documented that patients who underwent sentinel lymph node biopsy (SLNB), showed that the prevalence of SLN metastases had an inverse relationship with a lack of progesterone receptors [17]. The ER and PR levels do not contribute to the prediction of lymph node metastases since there was no correlation with node positivity [18].…”
Section: Discussionmentioning
confidence: 99%
“…higher than breast cancers of any other ERPRHER-2 phenotype (OR = 2.309). Triple positive breast tumours were diagnosed at a younger age and tumour characteristics like tumour size and grade could have been the main reason for this higher probability of ALN involvement [26][27][28][29][30][31][32]. However, the multivariate logistic regression analysis identified ''being triple positive'' as an independent predictor for lymph node involvement.…”
Section: Methodsmentioning
confidence: 96%